Data_Sheet_1_Spatial Distribution of Arctic Bacterioplankton Abundance Is Linked to Distinct Water Masses and Summertime Phytoplankton Bloom Dynamics (Fram Strait, 79°N).doc - Magda G. Cardozo-Mino; Eduard Fadeev; Verena Salman-Carvalho; Antje Boetius (2021)
The Arctic is impacted by climate warming faster than any other oceanic region on Earth. Assessing the baseline of microbial communities in this rapidly changing ecosystem is vital for understanding the implications of ocean warming and sea ice retreat on ecosystem functioning. Using CARD-FISH and semi-automated counting, we quantified 14 ecologically relevant taxonomic groups of bacterioplankton (Bacteria and Archaea) from surface (0–30 m) down to deep waters (2,500 m) in summer ice-covered and ice-free regions of the Fram Strait, the main gateway for Atlantic inflow into the Arctic Ocean. Cell abundances of the bacterioplankton communities in surface waters varied from 10 5 cells mL –1 in ice-covered regions to 10 6 cells mL –1 in the ice-free regions. Observations suggest that these were overall driven by variations in phytoplankton bloom conditions across the Strait. The bacterial groups Bacteroidetes and Gammaproteobacteria showed several-fold higher cell abundances under late phytoplankton bloom conditions of the ice-free regions. Other taxonomic groups, such as the Rhodobacteraceae, revealed a distinct association of cell abundances with the surface Atlantic waters. With increasing depth (>500 m), the total cell abundances of the bacterioplankton communities decreased by up to two orders of magnitude, while largely unknown taxonomic groups (e.g., SAR324 and SAR202 clades) maintained constant cell abundances throughout the entire water column (ca. 10 3 cells mL –1 ). This suggests that these enigmatic groups may occupy a specific ecological niche in the entire water column. Our results provide the first quantitative spatial variations assessment of bacterioplankton in the summer ice-covered and ice-free Arctic water column, and suggest that further shift toward ice-free Arctic summers with longer phytoplankton blooms can lead to major changes in the associated standing stock of the bacterioplankton communities.